Ghosting the news : local journalism and the crisis of American democracy - Sullivan, Margaret, 1957- (Columbia Global Reports, 2020)
"Ghosting the News tells the most troubling media story of our time: How democracy suffers when local news dies. Reporting on some of the news-impoverished areas in the U.S. and around the world, America's premier media critic, Margaret Sullivan, charts the contours of the damage but also surveys some new efforts to keep local news alive-from non-profit digital sites to an effort modeled on the Peace Corps. No nostalgic paean to the roar of rumbling presses, Ghosting the News instead sound a loud alarm, alerting citizens to the growing crisis in local news that has already done serious damage. If local newspapers are on the brink of extinction, we ought to know the full extent of the losses now, before it's too late"--